2011
DOI: 10.1107/s1600536811052020
|View full text |Cite
|
Sign up to set email alerts
|

Silver diaquacobalt(II)catena-borodiphosphate(V) hydrate, (Ag0.79Co0.11)Co(H2O)2[BP2O8]·0.67H2O

Abstract: The structure of the title compound, (Ag0.79Co0.11)Co(H2O)2[BP2O8]·0.67H2O is isotypic to that of its recently published counterparts AgMg(H2O)2[BP2O8]·H2O and (Ag0.57Ni0.22)Ni(H2O)2[BP2O8]·0.67H2O. It consists of infinite borophos­phate helical ribbons [BP2O8]3−, built up from alternate BO4 and PO4 tetra­hedra arranged around the 65 screw axes. The vertex-sharing BO4 and PO4 tetra­hedra form a spiral ribbon of four-membred rings in which BO4 and PO4 groups alternate. The ribbons are connected through slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The lithium-and sodium-cobalt members of the helical BPO family were reported previously (Shi, Shan, Dai et al, 2003;Menezes et al, 2008b). In addition, Zouihri et al (2012) have recently reported the structure of (Ag 0.79 Co 0.11 )Co(-H 2 O) 2 BP 2 O 8 Á0.67H 2 O, where Co and Ag share the same site. We report here the structures of the potassium and potassiumcalcium cobalt borophosphates, KCo(H 2 O) 2 BP 2 O 8 ÁyH 2 O (y ' 0.5), (I), and K 0.17 Ca 0.42 Co(H 2 O) 2 BP 2 O 8 ÁH 2 O, (II), grown hydrothermally and characterized by qualitative energydispersive X-ray (EDX) spectroscopic analysis and singlecrystal X-ray diffraction.…”
mentioning
confidence: 67%
“…The lithium-and sodium-cobalt members of the helical BPO family were reported previously (Shi, Shan, Dai et al, 2003;Menezes et al, 2008b). In addition, Zouihri et al (2012) have recently reported the structure of (Ag 0.79 Co 0.11 )Co(-H 2 O) 2 BP 2 O 8 Á0.67H 2 O, where Co and Ag share the same site. We report here the structures of the potassium and potassiumcalcium cobalt borophosphates, KCo(H 2 O) 2 BP 2 O 8 ÁyH 2 O (y ' 0.5), (I), and K 0.17 Ca 0.42 Co(H 2 O) 2 BP 2 O 8 ÁH 2 O, (II), grown hydrothermally and characterized by qualitative energydispersive X-ray (EDX) spectroscopic analysis and singlecrystal X-ray diffraction.…”
mentioning
confidence: 67%
“…Within the A x M y (H 2 O) 2 [BP 2 O 8 ]Áz(H 2 O) series, borophosphates with the following cations have been reported: A I = Li, Na, K, Rb, Cs, H 3 O, Ag and NH 4 ; A II = Ca; M II = Mg, Sc, Mn, Fe, Co, Ni, Cu, Zn, Cd; and M III = Fe, In (Ge et al, 2003(Ge et al, , 2005Yang et al, 2010;Yilmaz et al, 2000Yilmaz et al, , 2005Wang, 2008;Boy & Kniep, 2001a,b;Menezes et al, 2007Menezes et al, , 2008Zouihri et al, 2011aZouihri et al, ,b, 2012Guesmi & Driss, 2012;Zheng & Zhang, 2009;Ewald et al, 2006;Baykal et al, 2000;Boy et al, 2001a,b;Boy, Stowasser et al, 2001;Kniep et al, 1997;Zhuang et al, 2008;Engelhard, 2000;Schä fer et al, 2002;Lin et al, 2008). However, the structural data for members of this family with large alkaline cations Rb + and Cs + have not been presented in the literature, to our knowledge.…”
Section: Introductionmentioning
confidence: 99%